Electronic Spectroscopy And Its Interpretation - Thakur, Pramod Kumar (Himalayan Physics, 2015)
Electronic Spectroscopy relies on the quantized nature of energy states. At given enough energy, an electron can be excited from its initial ground state or initial excited state (hot band) and briefly exist in a higher energy excited state. Electronic transitions involve exciting an electron from one principle quantum state to another. Without incentive, an electron will not transition to a higher level.. The Himalayan Physics Vol. 5, No. 5, Nov. 2014 Page: 112-115